Tryptamine Attenuates Experimental Multiple Sclerosis Through Activation of Aryl Hydrocarbon Receptor - Dopkins, Nicholas; Becker, William; Miranda, Kathryn; Walla, Mike; Nagarkatti, Prakash; Nagarkatti, Mitzi (Frontiers in Pharmacology, 2021)
Tryptamine is a naturally occurring monoamine alkaloid which has been shown to act as an aryl hydrocarbon receptor (AHR) agonist. It is produced in large quantities from the catabolism of the essential amino acid tryptophan by commensal microorganisms within the gastrointestinal (GI) tract of homeothermic organisms. Previous studies have established microbiota derived AHR ligands as potent regulators of neuroinflammation, further defining the role the gut-brain axis plays in the complex etiology in multiple sclerosis (MS) progression. In the current study, we tested the ability of tryptamine to ameliorate symptoms of experimental autoimmune encephalomyelitis (EAE), a murine model of MS. We found that tryptamine administration attenuated clinical signs of paralysis in EAE mice, decreased the number of infiltrating CD4+ T cells in the CNS, Th17 cells, and ROR T cells while increasing FoxP3+Tregs. To test if tryptamine acts through AHR, myelin oligodendrocyte glycoprotein (MOG)-sensitized T cells from wild-type or Lck-Cre AHRflox/flox mice that lacked AHR expression in T cells, and cultured with tryptamine, were transferred into wild-type mice to induce passive EAE. It was noted that in these experiments, while cells from wild-type mice treated with tryptamine caused marked decrease in paralysis and attenuated neuroinflammation in passive EAE, similar cells from Lck-Cre AHRflox/flox mice treated with tryptamine, induced significant paralysis symptoms and heightened neuroinflammation. Tryptamine treatment also caused alterations in the gut microbiota and promoted butyrate production. Together, the current study demonstrates for the first time that tryptamine administration attenuates EAE by activating AHR and suppressing neuroinflammation.